Effect of Environmental Factors on Learning Quality Among Adult College Students: The Mediation Role of Learning Motivation (Journal of Education and Development, 2023)
In order to explore the impact of school environment and working organization environment on the learning quality of adult college students, 629 students from two adult colleges were randomly selected as participants in this study. The questionnaires of school environment, work organization environment, learning motivation and learning quality questionnaires were filled out by participants online. Statistical analysies were conducted on SPSS26.0 and PROCESS3.5. Results showed that school environment and work environment both positively predicted the learning quality of adult college students; learning motivation of adult college students played a partial mediation role between school environment, work environment and learning quality. Based on the findings, educators and enterprises should work together to create positive learning environments that inspires students’ learning motivation and improve their learning quality.